Interaction of selected fungicides with insoluble bovine skin collagen in the presence of the non ionic surfactant Triton X-100 - Fowler, William Mackenzie (Rhodes University, Faculty of Science, Department of Chemistry, 1992)
In the leather industry fungicides are often used for the protection of wet-blue leather. These fungicides are usually only sparingly soluble and are therefore formulated together with surfactants in order to increase their solubility and to ensure an even distribution over the surface of the hide after treatment. Solutions containing both fungicides and surfactant are complex. The nature of these solutions was investigated. By means of UV/Vis spectroscopy and viscometry it was shown that the surfactant and fungicides form micelles and mixed micelles in solution. The nature of these micelles and mixed micelles was dependent on the solution temperature as well as on the concentrations of the surfactant and fungicides. At the higher temperatures and concentrations transition to large, possibly rod-shaped, mixed micelles occurred. The interaction between the selected fungicides 2-(thiocyanomethylthio)benzothiazole and n-octyl-4-isothiazol-3-one with bovine skin collagen in the form of both limed and lightly chromed hide powder in the presence of the non ionic surfactant Triton X -100 was investigated. Fungicide uptake was determined by difference measurements on the float solutions at regular intervals during treatment. Binding was rapid with equilibrium being established within the first six hours even for the solutions with the highest surfactant concentration. Binding failed to follow a normal mass-action binding-type isotherm approaching a saturation limit, but increased continuously indicating a co-operative effect whereby binding site affinity actually increased with the amount of ligand bound. Binding was accompanied by a drop in the free surfactant in the solution at the higher biocide levels indicating the formation of complex mixed micelles which bind to the collagen fibres. The uptake and antifungal activity of commercial fomulations of the fungicides on chrome-tanned wet-blue leather was investigated at various treatment temperatures. At lower fungicide treatment concentrations, binding tended to follow a typical mass-action type binding isotherm, increasing slightly with temperature. At higher float concentrations, an inflexion point was apparent beyond which uptake showed a marked increase with concentration. This inflexion point, signifying a change in binding characteristics, occurred at progressively lower concentrations with increasing temperature. Antifungal activity in terms of storage periods to onset of fungal growth was determined on the wet-blue leather cuttings immediately after treatment and drainage and also on sample discs after exhaustive extraction of free fungicide using dichloromethane. Storage performance testing of the various treated wet-blue leathers was carried out by different methods. Residual protective periods showed a curvilinear increase with dosage offer and surface uptake. In the low dosage range treatment temperature had only a relatively slight effect in promoting uptake and improving storage protection. At higher dosages, the influence of temperature on uptake and storage protection was greater due to the increase in surface binding of the fungicides at the elevated temperatures. Only a portion of the fungicide uptake was recovered by direct solvent extraction of the treated wet-blue leather. Solvent extraction reduced storage margins. The storage response in relation to fungicide content was, however comparable after extraction, indicating that both irreversibly bound and physically associated fungicide offered effective protection. Results of the study provide further insight into the mode of interaction of fungicide emulsion dispersion with bovine skin collagen, and the importance of the emulsion dispersions and its stability in determining the uptake of fungicide.
Keywords: Collagenases -- Research; Fungicides -- Research; Hides and skins -- Preservation